Nuclear distribution and chromatin association of DNA polymerase α-primase is affected by TEV protease cleavage of Cdc23 (Mcm10) in fission yeast - Yang, X; Gregan, J; Lindner, K; Young, H; Kearsey, S (Biomed Central Ltd., 2005)
Background: Cdc23/Mcm10 is required for the initiation and elongation steps of DNA replication but its biochemical function is unclear. Here, we probe its function using a novel approach in fission yeast, involving Cdc23 cleavage by the TEV protease. Results: Insertion of a TEV protease cleavage site into Cdc23 allows in vivo removal of the C-terminal 170 aa of the protein by TEV protease induction, resulting in an S phase arrest. This C-terminal fragment of Cdc23 is not retained in the nucleus after cleavage, showing that it lacks a nuclear localization signal and ability to bind to chromatin. Using an in situ chromatin binding procedure we have determined how the S phase chromatin association of DNA polymerase α-primase and the GINS (Sld5-Psf1-Psf2-Psf3) complex is affected by Cdc23 inactivation. The chromatin binding and sub-nuclear distribution of DNA primase catalytic subunit (Spp1) is affected by Cdc23 cleavage and also by inactivation of Cdc23 using a degron allele, implying that DNA polymerase α-primase function is dependent on Cdc23. In contrast to the effect on Spp1, the chromatin association of the Psf2 subunit of the GINS complex is not affected by Cdc23 inactivation. Conclusion: An important function of Cdc23 in the elongation step of DNA replication may be to assist in the docking of DNA polymerase α-primase to chromatin.